Comparison of two suicide screening instruments for identifying high-risk individuals in prison - Hausam, Joscha; Calvano, Daniela; Opitz-Welke, Annette (Frontiers in Psychiatry, 2024)
Increased suicide rates in prison are a serious concern. Early identification of inmates at risk is a component of effective suicide prevention. The present study examined two suicide screening instruments in a sample of men in the Berlin, Germany, prison system (n = 289). The Screening for Initial Risk Assessment (SIRAS) identified significantly more high-risk inmates than the Vienna Instrument for Suicidality in Correctional Institutions (VISCI) (66 vs. 24). The results further show that the agreement in the classification was evident only in inmates with suicidal ideation, but was otherwise quite low. This can be explained by the fact that the instruments differ in terms of the risk factors taken into account. Finally, it was found that inmates classified as high risk received more monitoring and psychiatric or psychological support, which supports the construct validity of the instruments. As there were no deaths by suicide in the sample, no statistical information on the predictive validity of the instruments could be provided. Although research in this area is challenging, methodologically sound studies are needed to inform practice.